Benefits and challenges of marketing digitization strategy for telecommunication in Malaysia - Wong, Chin Phang (2020)
Digital marketing is related to marketing activities of companies on various digital platforms. The word digital is related to connecting through wires and technology. In this assignment an attempt has been made to evaluate digital marketing strategies involved in marketing activities of telecommunication companies of Malaysia. The benefits and challenges are identified with the view to bring creativity in digital marketing activities. The sample of 10 persons are drawn in form of five persons two focused groups. These were interviewed and them data was analyzed by following qualitative analysis method. The results claimed that there is significant impact of marketing digitization strategy on telecommunication companies of Malaysia. For this purpose, the challenges and benefits are also discussed.